Analisis Dampak Implementasi Lean Hospital Terhadap Pelayanan Pasien Instalasi Rawat Jalan Rumah Sakit di Indonesia: Studi Literatur - Kania Rizqita Dewi; Putri Regita Miolda; Triayu Nur Afifah; Acim Heri Iswanto (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2023)
. Outpatient installation services are a reflection of the services of a hospital. Several hospitals have implemented Lean Hospital for outpatient patient services. Lean Hospital is used to improve the quality of service to patients by reducing waste such as waste of waiting, defects, transportation, motion, inventory, and others. This study aims to analyze the impact of Lean Hospital implementation on outpatient patient care in hospitals in Indonesia. This research method uses the literature review method which is sourced from several online sites such as Google Scholar and journal databases, such as Garuda. Based on the results of the study it can be concluded that the implementation of Lean Hospital in outpatient services in hospitals has a positive impact on patients and health care workers, namely being able to identify and minimize waste and shorten the flow of patient services in all outpatient service units so as to reduce waiting time. In addition, the implementation of Lean Hospital also has a direct impact on a hospital's services, namely being able to improve service quality by providing better, faster, but cheaper (efficient) services and can increase patient satisfaction with hospital services.